Tectonic Consequences of a Uniformly Hot Backarc and Why is the Cordillera Mountain Belt High? - Hyndman, Roy D (Geoscience Canada, 2015)
SUMMARY Why is the North American Cordilleran mountain belt high? We expect a thick crust to support high elevations by isostasy but, remarkably, the Cordilleran crust is thin. There is no crustal root. An important recent recognition is that the high elevation is supported by thermal expansion rather than by thickened crust. The elevation of the Cordillera is only one consequence of the Cordillera being uniformly hot and having a thin lithosphere, in common with most current or recent backarcs. Some other consequences of the high temperatures compared to the adjacent cool craton include: (1) The Cordillera and other backarcs are hot, weak mobile belts that can be deformed by available plate-tectonic forces, in contrast to stable cratons that cannot; (2) Most continental seismicity is concentrated in backarcs; (3) In the Cordillera there is widespread sporadic ‘backarc’ volcanism; (4) The high temperatures result in very low strength in the lower crust that allows lower-crust detachment; (5) The lower crust weakness facilitates large-scale crustal oroclines that may be independent of the upper mantle; (6) The lower crust in the Cordillera and other backarcs is in amphibolite- to granulite-facies conditions, ~800–900°C at the Moho; (7) In ancient backarcs globally, regional Barrovian metamorphism is concluded to be the result of high temperatures that predate the orogenic collision and deformation. No "heat of orogeny" is required. Following the termination of subduction, backarcs cool with a time constant of 300–500 m.y. RÉSUMÉ Pourquoi la chaîne de montagnes de la Cordillère nord-américaine est-elle si haute? On comprend qu’une croûte sur-épaisse puisse expliquer une grande élévation, mais voilà, la croûte de la Cordillère est mince. Il n’existe pas de racine crustale. Or, récemment, une conclusion importante s’est imposée, soit que cette haute élévation s’explique par l’expansion thermique plutôt que par l’existence d’une croûte sur-épaisse. L’élévation de la Cordillère n’est qu’une des conséquences d’une Cordillère uniformément chaude flottant sur une lithosphère mince, caractéristiques communes aux zones d’arrière-arc actuelles ou récentes. Quelques unes des autres conséquences de cette haute température, par opposition aux froids cratons adjacents, comprennent: (1) La Cordillère et d’autres zones d’arrières-arcs sont des zones chaudes et facilement déformables par les forces tectoniques ambiantes, contrairement aux cratons stables; (2) La majorité de l’activité sismique continentale est concentrée dans le zones d’arrière-arc; (3) Dans la Cordillère l’activité volcanique sporadique est généralisé; (4) Ces températures élevées explique la très faible rigidité de la croûte inférieure et les décollements qu’elle subit; (5) La flaccidité de la croûte inférieure facilite la formation d’oroclinaux de grandes magnitudes qui peuvent être indépendants du manteau supérieur; (6) La croûte inférieure de la Cordillère et d’autres zones d’arrière-arc sont dans la zone de faciès amphibolite à granulite, soit 800 à 900oC à la discontinuité Moho; (7) Globalement dans les anciennes zones d’arrière-arc, le métamorphisme régional barrovien s’explique alors comme étant le résultat des hautes températures antérieures à la collision et à la déformation orogénique. Aucune « chaleur orogénique » n’est nécessaire. Après la période de subduction, les zones d’arrière-arc se refroidissent à l’intérieur d’un intervalle de temps de 300 à 500 millions d’années.